Evaluation of Improvement in Exercise Capacity after Pulmonary Endarterectomy in Patients with Chronic Thromboembolic Pulmonary Hypertension: Correlation with Echocardiographic Parameters - KEPEZ, ALPER; YILDIZELİ, BEDRETTİN; ÖZBEN SADIÇ, BESTE; MUTLU, BÜLENT; SÜNBÜL, MURAT (GEORG THIEME VERLAG KG, 2014)
BackgroundThe study evaluates the alterations in exercise capacity of chronic thromboembolic pulmonary hypertension (CTEPH) patients after pulmonary endarterectomy (PEA) and investigates the echocardiographic parameters associated with the degree of functional recovery. MethodsThirty consecutive patients with the diagnosis of CTEPH (17 males; mean age, 45.915.1 years) who had been referred for PEA operation were included in the study. Each patient underwent transthoracic echocardiography and 6-minute walk test (6-MWT) before and 6 months after PEA. ResultsAfter PEA, 6-MWT distances significantly increased (242.8 +/- 112.8 m vs. 423.6 +/- 89.1 m, p<0.001), whereas systolic pulmonary artery pressures and right ventricular dimensions significantly decreased (86 +/- 25.1mm Hg vs. 41.9 +/- 15.6mm Hg, p<0.001 and 42.1 +/- 10.1mm vs. 35.3 +/- 5.6mm, p<0.001, respectively). Magnitude of change in 6-MWT distance (-6-MWT) was found to be correlated with concomitant change in tricuspid annular plane systolic excursion and left ventricular myocardial performance index (r: 0.518, p: 0.004 and r: -0.385, p: 0.043, respectively). Linear regression analysis revealed preoperative 6-MWT distance as an independent negative predictor of delta-6-MWT (beta: -0.89, t: -3.97, p: 0.001). ConclusionCTEPH patients with more severely depressed exercise capacity at baseline displayed relatively greater degree of functional recovery after PEA in our study. Improvement in functional capacity was found to be correlated with improvement in parameters reflecting right ventricular functions rather than improvement in pulmonary artery pressure after PEA operation.
Keywords: chronic thromboembolic pulmonary hypertension; echocardiography; pulmonary endarterectomy; right ventricle; VENTRICULAR FUNCTION; DISPLACEMENT